Synthesis and properties of a novel family of liquid crystalline building blocks based on 5,5'-substituted-2,2'-bipyridine - Douce, Laurent; Ziessel, Raymond; Seghrouchni, Rachid; Skoulios, Antoine; Campillos, Eduardo; Deschenaux, Robert (My University, 1995)
Novel liq. cryst. compds. based on 5-methyl-5'-(4-n-alkoxyphenylvinyl)-2,2'-bipyridine were synthesized and their mesomorphic properties studied. All members of this series exhibit nematic, smectic A and smectic B phases. For the octyloxy compd. an hexatic phase is also obsd. [on SciFinder(R)]
Keywords: liq crystal property methyl alkoxyphenylvinyl bipyridine